2016
DOI: 10.1074/jbc.m116.731521
|View full text |Cite
|
Sign up to set email alerts
|

Elmo2 Is a Regulator of Insulin-dependent Glut4 Membrane Translocation

Abstract: Elmo2, a member of the Elmo protein family, has been implicated in the regulation of Rac1 and Akt activation. Recently, we found that Elmo2 specifically interacts with ClipR-59. Because Akt and Rac1 have been implicated in insulin dependent Glut4 membrane translocation, we hypothesize here that Elmo2 may play a role in insulin-dependent Glut4 membrane translocation. Accordingly, we found that overexpression of Elmo2 enhanced, whereas its knockdown suppressed, insulin-dependent Glut4 membrane translocation in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…51 Recently, it has been shown that ELMO2 is required for insulin-induced Rac1 GTP loading. 52 It has been reported that there is differential distribution of ELMO1 and ELMO2 in the developing mouse brain. 53 Little is known about GPCR-mediated ELMO2 function in these processes.…”
Section: Gpcr-mediated Functions Of Elmo/dock Complexes In Mammalian mentioning
confidence: 99%
“…51 Recently, it has been shown that ELMO2 is required for insulin-induced Rac1 GTP loading. 52 It has been reported that there is differential distribution of ELMO1 and ELMO2 in the developing mouse brain. 53 Little is known about GPCR-mediated ELMO2 function in these processes.…”
Section: Gpcr-mediated Functions Of Elmo/dock Complexes In Mammalian mentioning
confidence: 99%
“…Previous studies have described the ELMO proteins as promotors for RAC1 activity (Gumienny et al, 2001;Brugnera et al, 2002;Katoh and Negishi, 2003;Cetinkaya et al, 2016;Tran et al, 2021) and RAC1 was shown to be an important regulator of the glucose homeostasis by ensuring the vesicular insulin transport by organizing the pancreatic cytoskeleton during glucose induced insulin secretion (Kowluru, 2011;Møller et al, 2019). Furthermore, a lack of RAC1 is associated with insulin resistance in humans and rodents (Sylow et al, 2013;Sylow et al, 2014;Raun et al, 2018) and ELMO2 and RAC1, both regulate the insulin dependent membrane translocation of the glucose transporter 4 (GLUT4) in muscle cells (Sun et al, 2016). To address the question if Elmo1, Elmo2 or Elmo3 maintain glucose homeostasis in zebrafish, whole body glucose content of larval (120 hpf) and blood glucose levels of adult (7-15 mpf) elmo1 −/− , elmo2 −/− , and elmo3 −/− zebrafish were measured (Figure 6).…”
Section: Elmo1 Regulates Adult Blood Glucose Homeostasis In Zebrafishmentioning
confidence: 99%
“…Studies analyzing the role of ELMO1 in kidney function described an aggravation of nephropathy in mice with type 1 diabetes (Shimazaki et al, 2005;Hathaway et al, 2016) and a promotion of glomerular injury through dysregulation of the extracellular matrix (ECM) (Shimazaki et al, 2006) in presence of ELMO1. ELMO2 was shown to regulate the insulin dependent expression and membrane translocation of GLUT4 in human skeletal muscle cells and adipocytes, indicating a potential involvement in glucose homeostasis (Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The glucose uptake assay was carried out according to the protocols described before. 7 Briefly, cells were deprived with serum-free DMEM incubation for 3 hours and treated with our without 100 nmol/L insulin for 45 min. Cells were then incubated with Krebs buffer (containing 50 mmol/L HEPES (hydroxyethyl piperazineethanesulfonic acid), 4.7 mmol/L KCl, 1.25 mmol/L CaCl 2 , 1.25 mmol/L MgSO 4 , 136 mmol/L NaCl, pH=7.4) and 1 μmol/L 2-[ 3 H] deoxyglucose (Thermo) for 5 min.…”
Section: Cultured L6 Cells Glucose Uptake Evaluationmentioning
confidence: 99%
“…The subcellular fractionations of cultured L6 cells were performed per the descriptions from a previous investigation. 7 L6 cells were suspended in HES I buffer (pH=7.6) containing 0.25 mmol/L sucrose, 1 mmol/L EDTA, 20 mmol/L Tris and protease inhibitor cocktail (Abcam). Cells were homogenized and then centrifuged at 19 000 g at 4°C for 20 min.…”
Section: Subcellular Fractionationmentioning
confidence: 99%